2021
DOI: 10.1016/j.crgsc.2021.100159
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of Phyllanthus amarus phytochemicals as potent drugs against SARS-CoV-2 main protease

Abstract: Phyllanthus amarus , also known as Bhui Korma in India, is well known for its medicinal properties and is used to treat several diseases worldwide. This study aims to identify phytochemicals from P. amarus and assess their anti-viral activity through in silico methods against the main protease (M Pro ) enzyme of the novel coronavirus. 190 compounds were obtained from literature and docked against 3CLPro and 16 compounds showed grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Nevertheless, about the end of simulation, the optimum SASA peaks were observed that indicate that by the end of the simulation more of the ligand is interred into the protein, rather than interacting with the aqueous environment (Martins et al., 2014). Accordingly, the suitable plots of free energy of solvation energy, average angle interaction and distribution indicate the compatibilities with the pocket of active site (Murthy et al., 2021). The cuminaldehyde is a key ingredient of the cumin that was reported to have antimicrobial, antioxidants, anti‐inflammatory and hypolipidemic potential (Morshedi et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, about the end of simulation, the optimum SASA peaks were observed that indicate that by the end of the simulation more of the ligand is interred into the protein, rather than interacting with the aqueous environment (Martins et al., 2014). Accordingly, the suitable plots of free energy of solvation energy, average angle interaction and distribution indicate the compatibilities with the pocket of active site (Murthy et al., 2021). The cuminaldehyde is a key ingredient of the cumin that was reported to have antimicrobial, antioxidants, anti‐inflammatory and hypolipidemic potential (Morshedi et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Indian medicinal plants have been known for their remarkable anti-inflammatory, anti-allergic, anti-bacterial, anti-fungal, immunomodulatory, and anti-viral inhibitory effects against a wide range of pathogenic infections [ 25 ]. Earlier, the extracts and phytochemical compounds of Decalepis hamiltonii, Acacia modesta, Hypericum perforatum, Phylanthus amarus, and Phyllanthus emblica have shown remarkable efficacy against viruses like chikungunya, hepatitis, herpes, and bronchitis [ 26 , 27 , 28 , 29 , 30 ]. Hence, new antiviral strategies must take advantage of the antiviral inhibitory properties of naturally occurring phytochemical compounds instead of focusing only on synthetic substances.…”
Section: Discussionmentioning
confidence: 99%
“…The 3CLpro/MPro activity site is found in the gap between domains I and II, consisting of a Cys-His catalytic dyad (Cys145 and His41) [48]. The active pocket consists of hydrophobic amino acids such as Tyr54, Met49, Met165, Phe140, Leu141, Cys145, Leu27, Pro168, Leu167, Cys145, Ala191, Cys44, Leu50, and Met40, which provide a relatively hydrophobic environment to contain the compound and stabilize its conformation.…”
Section: In Silico Determination Of Biological Activity and Molecular...mentioning
confidence: 99%
“…Validation of the molecular docking protocols for the crystal structure of the main protease (Mpro) COVID-19 in complex with 11b inhibitor *. According to Gowtham et al (2008) [44] and Hevener et al (2009)[45], the predicted binding mode using molecular docking indicates that when the RMSD is less than 2.0 Å in relation to the crystallographic pose of a respective ligand, the validation is considered satisfactory[46,47].The 3CLpro/MPro activity site is found in the gap between domains I and II, consisting of a Cys-His catalytic dyad (Cys145 and His41)[48]. The active pocket consists of…”
mentioning
confidence: 99%